(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article examines the specifics of using multisensory methods in the context of the early development system for children with disabilities. It analyzes scientifically based approaches to organizing the educational process that take into account the neuropsychological, sensory and cognitive characteristics of this category of children. Particular attention is paid to the integration of auditory, visual, tactile and kinesthetic stimuli as a key factor in the formation of stable intermodal connections. The importance of this approach for effective assimilation of information in the context of both inclusive and correctional education is emphasized.